Trademark Rights Dispute (Geprek Bensu With I Am Geprek & Singapore Company With Hadi Darsono) - Bonaraja Purba; Inda Serfina Tarigan; Noel Ramot Denvico Tamba; Nova Novita Pardede (PT FORMOSA CENDEKIA GLOBAL, 2023)
Legal protection of Intellectual Property Rights (IPR) is very important to encourage technological progress. By providing legal protection to writers, technology creators and artists, IPR can inspire people to create more. The research method used is descriptive qualitative research method. This research uses data sources that are written records, namely cases that occur and can be accessed freely on news media pages and so on. The results of this study explain that the settlement of intellectual property rights disputes over the culinary business brand Geprek Bensu with I Am Geprek Bensu based on the Commercial District Court has been decided by decision Number 57/Pdt. Sus. Brand/2019/PN Niaga Jkt Pst. The Supreme Court decided to reject Ruben Onsu's lawsuit and granted the reconception of PT Ayam Geprek Sujono.